(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This scientific article highlights the significant role of the periodical press in the study of the history of Uzbekistan during the years of independence. The article emphasizes how the periodical press contributed to historical research by disseminating historical knowledge, encouraging public engagement with history, and providing a platform for documenting key events and social changes. This article analyzes the activities of periodicals in Uzbekistan during the years of independence, highlighting their socio-political and cultural significance. It examines the role of periodicals in promoting the idea of independence and shaping national values and ideas. Positive and negative aspects of the functioning of modern print and electronic periodicals are also discussed.